Front Cover: Hybrid ZnSe‐SnSe2 Nanoparticles Embedded in N‐doped Carbon Nanocube Heterostructures with Enhanced and Ultra‐stable Lithium‐Storage Performance (ChemElectroChem 24/2021). Issue 24 (12th November 2021) - Yu, Litao; Kim, Kyung Su; Saeed, Ghuzanfar; Kang, Jun; Kim, Kwang Ho
Abstract : The Front Cover illustrates a type of novel hybrid bimetallic selenide composite embedded in N‐doped carbon nanocubes. It shows that carbon‐coated hybrid nanoparticles with more void space can help promote the formation of solid electrolyte interface (SEI) film, effectively protecting the nanostructures from pulverization and aggregation, thus leading to enhanced and ultra‐stable electrochemical performance as lithium‐ion battery anode materials. More information can be found in the Article by L. Yu et. al .